Proceedings of the 38th International ACM SIGIR Conference on Research and Development in Information Retrieval 2015
DOI: 10.1145/2766462.2767802
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Investigation into Fixed and Adaptive Stopping Strategies

Abstract: Most models, measures and simulations often assume that a searcher will stop at a predetermined place in a ranked list of results. However, during the course of a search session, real-world searchers will vary and adapt their interactions with a ranked list. These interactions depend upon a variety of factors, including the content and quality of the results returned, and the searcher's information need. In this paper, we perform a preliminary simulated analysis into the influence of stopping strategies when q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…In previous work, we performed an initial analysis comparing a fixed depth stopping strategy against two implementations of the frustration point/disgust rules [23]. The fixed depth stopping strategy assumed that the searcher would stop at a particular document n in the ranked list, regardless of whether previous documents were considered relevant or non-relevant.…”
Section: Related Workmentioning
confidence: 99%
“…In previous work, we performed an initial analysis comparing a fixed depth stopping strategy against two implementations of the frustration point/disgust rules [23]. The fixed depth stopping strategy assumed that the searcher would stop at a particular document n in the ranked list, regardless of whether previous documents were considered relevant or non-relevant.…”
Section: Related Workmentioning
confidence: 99%
“…the slope of the user's gain curve. For example, a possible user computable measure of the current rate of gain could be the number of relevant documents found in the last 3 examined results or perhaps the number of relevant documents found in the last 2 minutes, or some of the strategies proposed by Maxwell et al [8]. White and Dumais [14] conducted a study and found that 24% of search engine switches were a result of dissatisfaction and 23% were because of an expectation of better results, and many of the other reasons reflect some desire for more or different information.…”
Section: Discussionmentioning
confidence: 99%
“…As done in prior simulations [2,19], the decision to click on a snippet -and the subsequent decision to mark a document relevant -are based upon interaction probabilities. The clicking (P (C)) and marking (P (M )) probabilities used here are reported in Table 1(b).…”
Section: Snippet and Document Decision Makingmentioning
confidence: 99%